صيغ التمويل الإسلامي في ظل برنامج التنمية الاقتصادية في الجزائر (2014/2024) - بن مناد, يمينة (My University, 2021)
This study aims to clarify the role of Islamic finance formulas in achieving economic development by presenting various concepts, characteristics, foundations and others for both variables by adopting the descriptive analytical approach, in addition to presenting Algeria’s experience in the field of Islamic banking supported by an applied example of the real estate Murabaha formula in the applied aspect using a study approach status. The study reached a set of results, the most important of which is that Islamic finance contributes to diversifying non-oil financing sources, in addition to allocating the necessary capital to finance the economy by encouraging individuals to save and stay away from hoarding. The most important result was that Algeria’s experience is still young compared to the experiences of other countries. And perhaps what the 20-02 system brings is enough to make Islamic finance in Algeria a pioneer through the diversity of Islamic products offered and the ways to deal with them.
البنك الوطني الجزائري -وكالة مستغانم 878
Keywords: Islamic finance formulas, economic development